A telegeriatric service in a small rural hospital: A case study and cost analysis. (December 2015) - Versleijen, Marloes; Martin-Khan, Melinda G; Whitty, Jennifer A; Smith, Anthony C; Gray, Leonard C
Introduction: Small hospitals in rural areas usually have an insufficient caseload of frail old people to justify the regular presence of a geriatrician. This study examined the costs of providing a telegeriatric service by videoconference in a rural hospital, compared to the costs of a visiting geriatrician that travels to undertake in-person consultations. Methods: A cost analysis was undertaken to compare the costs of the telegeriatric service model with the costs of a visiting geriatrician service model. A recently established telegeriatric service at Warwick Hospital was used as a case study. Results: In the base case model (assuming four patients per round and a round-trip travel distance of 312 kilometres), an estimated AUD$131 per patient consultation can be saved in favour of the telegeriatric service model. Key drivers of costs are the number of patients per round and the travel distance and time in the visiting geriatrician model. At a workload of four patients per round, it is less expensive to conduct a telegeriatric service than a visiting geriatrician service when the round-trip travel time exceeds 76 minutes. Discussion: Even under quite conservative assumptions, a telegeriatric service offers an economically feasible approach to the delivery of specialist geriatric assessment in rural and remote settings.